2022
DOI: 10.29333/ejmste/12682
|View full text |Cite
|
Sign up to set email alerts
|

Interactive computer assessment and analysis of students’ ability in scientific modeling

Abstract: Scientific modeling (SM) is a core scientific practice and critical for students’ scientific literacy. Previous research has not used interactive computer assessment to investigate students’ SM ability. This study aimed to explore an effective way in human-computer interaction to reveal the challenges faced by students in the four-element process of constructing, using, evaluating, and revising models. Contextualized in the solar system, eleven interactive tasks assessed 419 students in grades 4, 7, and 10. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Comparing this assessment model to previous studies(Hardcastle et al, 2019;Justi, 2009;Lin et al, 2022;Mayer & Krajcik, 2021;Zhai et al, 2022), several distinctions can be observed. While previous studies have explored scientific modeling skill assessment, the current study goes beyond addressing the specific needs and requirements of Thai students.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…Comparing this assessment model to previous studies(Hardcastle et al, 2019;Justi, 2009;Lin et al, 2022;Mayer & Krajcik, 2021;Zhai et al, 2022), several distinctions can be observed. While previous studies have explored scientific modeling skill assessment, the current study goes beyond addressing the specific needs and requirements of Thai students.…”
mentioning
confidence: 57%
“…Several studies have been conducted on assessing scientific modeling skills (Hardcastle et al, 2019;Justi, 2009;Lin et al, 2022;Mayer & Krajcik, 2021;Zhai et al, 2022). For example, Hardcastle et al (2019) utilized a rubric scoring model to assess scientific modeling skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What students understand about the nature of scientists' work and the relationship between this understanding and students' motivation to pursue their future science-related careers needs more study. In addition, future research may need to explore the relationships between students' mental images of scientists' characters and the ways students engage in scientific practices such as argumentation (Chen et al, 2022;Phua & Tan, 2018), modeling (Ke & Schwarz, 2021;Lin et al, 2022), and sensemaking (Gutierez, 2019;Odden & Russ, 2019).…”
Section: Discussionmentioning
confidence: 99%